A discussion on the plausible role of ice streams in carving Martian outflow channels: Revisiting the earliest hypothesis by Lucchitta et al. (1981). (October 2022) - Sam, Lydia; Bhardwaj, Anshuman; Gharehchahi, Saeideh
Linear, incised and usually an order of magnitude wider than the Martian valleys, the Martian outflow channels are scoured ground commonly displaying streamlined remnants of the pre-existing terrain. A recent study used an unprecedented dataset of the Martian valley networks to propose that most of the valley networks are a result of combined surface and subglacial runoff. This also prompts to revisit One of the earliest hypotheses that the ancient ice streams might have carved the Martian outflow channels. With an exceptional focus on Mars exploration planned during the next decades, it is important to assess the regional-scale geomorphic processes to better target the future landing and sample return missions.